Representasi Feminisme dalam Film Mulan 1998 - Mawar Desnia Suparman (PENAOQ: Jurnal Sastra, Budaya dan Pariwisata, 2022)
This study aims to analyze the 1998 Mulan movie, directed by Robert D. San Souci, which was produced by Walt Disney Pictures with the theme of women's emancipation. This study uses a qualitative approach with semiotic data analysis techniques. In this study, the data source used as the object of analysis was the Mulan movie by Robert D. San Souci. The symbols contained in the film were analyzed using Roland Barthes' semiotic approach, namely the denotation and connotation stages. This analysis focuses on the feminist thought of the Chinese people and traditional culture. The results of the research show that the feminism that is raised in the 1998 Mulan movie is liberal feminism and existentialist feminism. The character Mulan fights patriarchal ideology by leaving her hometown and replacing her ailing father to represent her family in the war against the Hun invaders ordered by the emperor. This Mulan movie depicts the phenomenon of women experiencing gender inequality in terms of marginalization, subordination, stereotypes, violence, and double workload. This movie also teaches us that a woman can give honor to her family and has the right to be responsible for herself.